2007
DOI: 10.1038/sj.bjp.0707512
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glucocorticoids control neutrophil mobilization from bone marrow to blood and tissues in non‐inflammatory conditions

Abstract: Background and purpose: We have shown that endogenous glucocorticoids control neutrophil mobilization in the absence of inflammation. In this study the role of the glucocorticoid receptor (GR) in the physiological control of neutrophil mobilization was investigated, focusing on the specific mechanisms for mature neutrophils in bone marrow, circulating neutrophils and endothelial cells. Experimental approach: Male Wistar rats were treated with RU 38486 or adrenalectomized. Cell numbers in bone marrow and circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 46 publications
3
45
0
9
Order By: Relevance
“…The same pattern of leukocyte trafficking is induced by high concentrations of synthetic glucocorticoid or by injection of adrenocorticotropic hormone (ACTH) [20,21]. Interestingly, in the absence of stress conditions, neutrophilia has also been detected in animals deficient in glucocorticoid activity [22,23], indicating the existence of a tight physiological control on neutrophil trafficking by secreted glucocorticoids.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The same pattern of leukocyte trafficking is induced by high concentrations of synthetic glucocorticoid or by injection of adrenocorticotropic hormone (ACTH) [20,21]. Interestingly, in the absence of stress conditions, neutrophilia has also been detected in animals deficient in glucocorticoid activity [22,23], indicating the existence of a tight physiological control on neutrophil trafficking by secreted glucocorticoids.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, the molecular interactions of bone marrow granulocytes, stromal cells, sinusoids and microvessels are under the control of chemical mediators of stress [37,38,39,40]. We and others have shown that secreted or exogenous glucocorticoids modulate both physiological and stress-mediated granulopoiesis and bone marrow granulocyte delivery [23,33,41]. Here we show that AnxA1, a protein secreted in response to glucocorticoid action, controls granulopoiesis and bone marrow/blood/bone marrow trafficking by modulating granulocyte maturation phases and the CXCR4/SDF-1α…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tem sido mostrado que os GE inibem a translocação nuclear do fator de transcrição NFkappa B na célula endotelial, que inibe a expressão gênica de imunoglobulinas (CAVALCANTI et. al., 2007) , e que a modulação sobre a L-selectina é dependente da anexina-1 (ANXA1), uma proteína antiinflamatória sintetizada pela ação dos GC (CAVALCANTI et. al., 2007;D'ACQUISTO,2009).…”
Section: -Glicocorticóides (Gc) E Recrutamento Leucocitáriounclassified
“…al., 1993;LIANG-SUO et. al., 2002;CAVALCANTI et. al., 2007;JURADO, 2009) e, assim, tem sido observado que sua meia-vida é superior a 24 horas e que o tratamento in vivo com RU 38486 exacerba os eventos da resposta inflamatória (LAUE et.…”
Section: -Discussãounclassified